ADMINISTRATIVE SYSTEM IN MATERNITY HOSPITAL PATIENT DATA NASYITHOH USING MICROSOFT VISUAL BASIC 6.0 - Nurhidayati Nurhidayati; Hariyanto, SKom, MMSI Hariyanto, SKom, MMSI (Jurnal Sistem Informasi, 2003)
In preparing this report the author wanted to propose to computerize Patient Data Collection System at the maternity hospital Nasyithoh, Tambun, Bekasi. For that it needs improvement in the data collection process alonghis reports, using computer facilities are expected to overcome existingsweaknesses in the system long.Processing of patient data using a computerized system and Microsoft Visual Basic 6.0 system will be more easily processed because the data has been arranged with the good and the time required is relatively short.